Coumarin in Brazilian cachaça stored in barrels of Amburana cearensis - Amazile Biagioni Maia; Lorena Simão Marinho; Lucas Oliveira Tonidandel; Frederico Marx Brom Carneiro; Elaine Cristina da Conceição; Bárbara Dias Machado (Current Perspectives in Agriculture and Food Science Vol. 5, 2023)
The purpose of this chapter was to determine how closely cachaça preserved in amburana barrels adhered to the real coumarin content limit set out by Brazilian and international law. In this chapter, the coumarin content of twelve commercial cachaças, whose labels specify storage in amburana wood barrels, was examined. The phenolic chemical coumarin (1,2-benzopyrone) is derived from plants. In addition to being widely utilized in human medicine, it is also employed as a bioactive ingredient in nutraceutical foods as well as an odorant in food, drinks, cosmetics, and fragrance. The beverage known as cachaça is made in Brazil by distilling sugarcane juice that has undergone fermentation. International health organizations advise a daily consumption cap of 0.1 mg/kg owing to the possibility of hepatotoxicity and other negative consequences in more susceptible individuals. Brazilian law has set a limit of 10 mg/kg for coumarin in alcoholic beverages, following a global trend. The average result for nine samples selected as most representative (18.0 ± 7.0 mg/L) was above the legal established limit. The results of three samples were disregarded, two for being much below (0.6 and 0.8 mg/L, respectively); and the third, for being much over the average (45.1 mg/L), with poor sensory quality and not suitable for commercialization. It was concluded that there is a need for more rigor in the identification of the wood species (Amburana cearensis) used in the manufacture of amburana barrels and for more effective control of the coumarin content transferred to the cachaça during storage in this wood.